Diagnosis and treatment coverage among hepatitis C infections in Denmark, 2022: a capture-recapture study using national registers - Signe Freja Storgaard; Inge Petersen; Gordon Hay; Signe Bollerup; Maria Wessman; Nina Weis; Lars Haukali Omland; Birgit Røge; Alex Lund Laursen; Lone Hagens Mygind; Henrik Krarup; Toke Seierøe Barfod; et al. (Infectious Diseases, 2026)

Participatory approaches in aquatic ecosystem services valuation: insights from a systematic literature review and future research perspectives - Tigran Keryan; Verena Radinger-Peer; Brenda Maria Zoderer; Rafaela Schinegger; Vardan Asatryan (Ecosystem Services, 2026)

Development of insects in newly established grassland over six years: Increased conservation benefits through diverse plant communities - Maria Peer; Sophie Kratschmer; Manuela Bürgler; Raja Imran Hussain; Dominik Rabl; Ronnie Walcher; Tobias Schernhammer; Bea Maas; Norbert Schuller; Nora Vogel; Matthias Heer; Simon Zwatz; et al. (Agriculture, Ecosystems & Environment, 2024)

Customized plant microbiome engineering for food security - Maria Batool; Lilia C. Carvalhais; Brendan Fu; Peer M. Schenk (Trends in Plant Science, 2024)

Bioremediation of rapid sand filters for removal of organic micropollutants during drinking water production - Peer H.A. Timmers; Wolter Siegers; Maria Lousada Ferreira; Paul W.J.J. van der Wielen (Water Research, 2024)

Evaluation of the cytotoxic and genotoxic potential of printer toner particles in a 3D air-liquid interface, primary cell-based nasal tissue model - Till Jasper Meyer; Nursen Tekin; Peter Hense; Totta Ehret-Kasemo; Nina Lodes; Manuel Stöth; Pascal Ickrath; Thomas Gehrke; Rudolf Hagen; Sofia Dembski; Michael Peer; Maria R. Steinke; et al. (Toxicology Letters, 2023)

Unexpected air pollutants with potential human health hazards: Nitrification inhibitors, biocides, and persistent organic substances - Johann G. Zaller; Maren Kruse-Plaß; Ulrich Schlechtriemen; Edith Gruber; Maria Peer; Imran Nadeem; Herbert Formayer; Hans-Peter Hutter; Lukas Landler (Science of The Total Environment, 2023)

Prospects and challenges of environmental DNA (eDNA) metabarcoding in mangrove restoration in Southeast Asia - Alison K. S. Wee; Severino G. Salmo III; Kannan Sivakumar; Amy Y-H Then; Mohammad Basyuni; Jean Fall; Kazi Ahsan Habib; Yukinobu Isowa; Venus Leopardas; Nasreen Peer; Maria D. Artigas-Ramirez; Kithsiri Ranawana; et al. (Frontiers in Marine Science, 2023)
Species detection using environmental DNA (eDNA) is a biomonitoring tool that can be widely applied to mangrove restoration and management. Compared to traditional surveys that are taxa-specific and time-consuming, eDNA metabarcoding offers a rapid, non-invasive and cost-efficient method for monitoring mangrove biodiversity and characterising the spatio-temporal distribution of multiple taxa simultaneously. General guidelines for eDNA metabarcoding are well-established for aquatic systems, but habitat-specific guidelines are still lacking. Mangrove habitats, as priority ecosystems for restoration in Southeast Asia, present unique prospects and challenges in these regards. Environmental DNA metabarcoding can be used to (1) track functional recovery in ecological restoration, (2) prioritise conservation areas, (3) provide early warning for threats, (4) monitor threatened taxa, (5) monitor response to climate change, and (6) support community-based restoration. However, these potential applications have yet been realized in Southeast Asia due to (1) technical challenges, (2) lack of standardised methods, (3) spatio-temporal difficulties in defining community, (4) data limitations, and (5) lack of funding, infrastructure and technical capacity. Successful implementation of eDNA metabarcoding in mangrove restoration activities would encourage the development of data-driven coastal management and equitable conservation programs. Eventually, this would promote Southeast Asia’s shared regional interests in food security, coastal defence and biodiversity conservation.

Increasing prevalence of chronic hepatitis B virus infection and low linkage to care in Denmark on 31 December 2016 – an update based on nationwide registers - Signe Bollerup; Maria Wessman; Janne Fuglsang Hansen; Stine Nielsen; Gordon Hay; Susan Cowan; Henrik Krarup; Lars Omland; Peter Jepsen; Nina Weis; Peer Brehm Christensen (Infectious Diseases, 2023)

Comparative proteomics of Geobacter sulfurreducens PCA T in response to acetate, formate and/or hydrogen as electron donor - Monir Mollaei; Peer H. A. Timmers; Maria Suarez‐Diez; Sjef Boeren; Antonie H. van Gelder; Alfons J. M. Stams; Caroline M. Plugge (Environmental Microbiology, 2021)
Summary Geobacter sulfurreducens is a model bacterium to study the degradation of organic compounds coupled to the reduction of Fe(III). The response of G. sulfurreducens to the electron donors acetate, formate, hydrogen and a mixture of all three with Fe(III) citrate as electron acceptor was studied using comparative physiological and proteomic approaches. Variations in the supplied electron donors resulted in differential abundance of proteins involved in the citric acid cycle (CAC), gluconeogenesis, electron transport, and hydrogenases and formate dehydrogenase. Our results provided new insights into the electron donor metabolism of G. sulfurreducens . Remarkably, formate was the preferred electron donor compared to acetate, hydrogen, or acetate plus hydrogen. When hydrogen was the electron donor, formate was formed, which was associated with a high abundance of formate dehydrogenase. Notably, abundant proteins of two CO 2 fixation pathways (acetyl‐CoA pathway and the reversed oxidative CAC) corroborated chemolithoautotrophic growth of G. sulfurreducens with formate or hydrogen and CO 2 , and provided novel insight into chemolithoautotrophic growth of G. sulfurreducens .